Excluir para proteger: la "guerra" contra la trata de personas y el tráfico de migrantes y las nuevas lógicas de control migratorio en Ecuador - Ruiz Muriel, Martha Cecilia; Álvarez Velasco, Soledad (El Colegio de México, 2019)
Far from conceiving that security and human rights, on one hand, and restriction and protection, on the other, are two exclusionary perspectives in international migration management, this article argues that both articulate and feed one another. Drawing on research on governmentality, we explore this articulation, while analysing anti-trafficking and anti-smuggling policies, core elements within regional and international migration agendas. We focus on Ecuador’s “Citizens Revolution” government. Based upon an ethnographic study, we reveal the role migrants smuggling and human trafficking have strategically played in the production of “risky migration” and “migrant irregularity”, and in justifying exceptional measures during particular conjunctures defined as “humanitarian crises”. We conclude that migration policies formulated during the Ecuadorean “post neoliberal” period are not wholly autonomous nor dissident, but functional to the global and hegemonic neoliberal migration control regime.